ANALISIS KEPUTUSAN PEMBELIAN PRODUK MAKANAN RINGAN IMPOR (STUDI KASUS : MAHASISWA FAKULTAS EKONOMI DAN BISNIS ISLAM UNIVERSITAS ISLAM NEGERI SULTAN THAHA SAIFUDDIN JAMBI) - Nurfitri Martaliah; Sri Rezeki; Efni Anita (Nusantara Hasana Berdikari, 2022)
This study reveals the analysis of purchasing decisions for imported snacks for students of the Islamic Economics and Business Faculty, Sultan Thaha Saifuddin State Islamic University, Jambi. The purpose of this study was to determine what influences purchasing decisions for imported snack products. This study uses a descriptive quantitative approach. The population in this study were students of the Islamic Economics and Business Faculty, Sultan Thaha Saifuddin State Islamic University Jambi and the sample as research respondents was taken using the slovin formula, namely 100 students. The data obtained in this study were analyzed using multiple linear regression analysis with the SPSS 25 program. The results of this study indicate that the calculated F value of 23,449 is greater than the F table of 2.31, which means simultaneously there is an effect on the halal label (X1), price ( X2) and promotion (X3) on purchasing decisions (Y).